Pengaruh Cash Ratio, Debt to Equity Ratio, dan Return On Assets Terhadap Return Saham dengan Nilai Tukar sebagai Variabel Moderating Pada Perusahaan Perkebunan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Yunan Surono; Andrian Hadinata (Universitas Batanghari, 2020)
The purpose of the research is to analyze the Influence of Cash Ratio, Debt To Equity Ratio and Return On Assets to Stock Return With Exchange Rate as Moderating Variables In Plantation Companies Listed In Indonesia Stock Exchange. This research uses descriptive analysis and statistical analysis methods. data that uses secondary data. This study focuses on the influence of 3 independent variables on the dependent variable by adding moderation variables to determine whether the moderating variable can affect the relationship between the independent variables on the dependent variable. Hypothesis testing in this study uses the F test and t test, with a brief significance level (a) 5%. This data analysis uses SPSS 20 data processing software for Windows. The population of this study is companies engaged in the plantation sector in the Indonesia Stock Exchange period 2014 - 2018, with a purposive sampling technique, obtained 6 companies that have fullfill criteria in this research. The results of this study partially Cash Ratio, Debt to Equity Ratio, and Return On Assets have a significant effect on stock returns, partially Debt to Equity Ratio and Return On Assets have a significant positive effect on stock returns, while Cash Ratio has no significant effect on stock returns. and the value is not able to affect the relationship between independent variable and dependent variable.